Risk stratification for febrile neutropenia in patients with testicular germ cell tumors. (19th January 2018) - Terbuch, Angelika; Posch, Florian; Partl, Richard; Zurl, Brigitte; Bauernhofer, Thomas; Pichler, Martin; Szkandera, Joanna; Hutterer, Georg C.; Pummer, Karl; Kapp, Karin S.; Stöger, Herbert; Gerger, Armin; et al.
Abstract: The aim of this study was to detect risk factors for febrile neutropenia (FN) in patients with testicular germ cell tumors (TGCT). In this retrospective cohort study at the Medical University of Graz, we included 413 consecutive TGCT patients who received adjuvant or curative treatment with cisplatin‐based chemotherapy. FN occurred in 70 (16.9%) of 413 patients. In univariable logistic regression, higher age (odds ratio (OR) per 5 years = 1.17, 95% CI: 1.02–1.35, P = 0.022), reduced performance status (PS) (OR = 2.73, 1.47–5.06, P = 0.001), seminomatous histology (OR = 2.19, 1.26–3.78, P = 0.005), poor IGCCCG risk class (OR = 4.20, 1.71–10.33, P = 0.002), and prior radiotherapy (pRTX) (OR = 8.98, 2.09–38.61, P = 0.003) were associated with a higher risk of FN. In multivariable analysis adjusting for age and risk classification, only poor PS (OR = 2.06, 1.05–4.03, P = 0.035), seminomatous histology (OR = 2.08, 1.01–4.26, P = 0.047), and pRTX (OR = 7.31, 1.61–33.17, P = 0.010) prevailed. In the subgroup of seminoma patients ( n = 104), only pRTX predicted for FN risk (OR = 5.60, 1.24–25.34, P = 0.025). Five of eight seminoma patients with pRTX developed FN (63%), as compared to 22 FN cases (23%) in the 96 seminoma patients without pRTX ( P = 0.027). The eight seminoma patients who received pRTX had significantly lower pre‐chemo white blood counts (4.7 vs. 6.5 G/L), neutrophil counts (3.2 vs. 4.3 G/L), and platelet counts (185 vs. 272 G/L) than patients without pRTX (all P < 0.0001). TGCT patients with a reduced performance status or who had been previously treated with radiotherapy have an increased risk for neutropenic fever during chemotherapy. Abstract : The aim of this study was to detect prognostic factors for febrile neutropenia (FN) in patients with testicular germ cell tumors. We identified (1) higher age, (2) poor performance status, (3) poor IGCCCG risk classification, and (4) prior radiotherapy in the seminoma subpopulation as risk factors for FN in patients with testicular cancer.